2021
DOI: 10.1016/j.envpol.2021.117962
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic speciation in rice bran: Agronomic practices, postharvest fermentation, and human health risk assessment across the lifespan

Abstract: Arsenic (As) exposure is a global public health concern affecting millions worldwide and stems from drinking water and foods containing As. Here, we assessed how agronomic practices and postharvest fermentation techniques influence As concentrations in rice bran, and calculated health risks from consumption. A global suite of 53 rice brans were tested for total As and speciation. Targeted quantification of inorganic As (iAs) concentrations in rice bran were used to calculate Target Hazard Quotient (THQ) and Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The mechanism is that aerobic conditions during the dry period of AWD promote the activity of As-methylating microorganisms in the soil, which preferentially methylate iAs to DMA over MMA. Weber et al [13] reported lower MMA (0.003 ± 0.004 mg kg −1 ) ( Table 1 ) in rice bran cultivated under AWD compared to that cultivated under CF (0.01 ± 0.006 mg kg−1). However contrary results have also been reported.…”
Section: Uptake and Transport Of As In Rice Plantsmentioning
confidence: 95%
See 4 more Smart Citations
“…The mechanism is that aerobic conditions during the dry period of AWD promote the activity of As-methylating microorganisms in the soil, which preferentially methylate iAs to DMA over MMA. Weber et al [13] reported lower MMA (0.003 ± 0.004 mg kg −1 ) ( Table 1 ) in rice bran cultivated under AWD compared to that cultivated under CF (0.01 ± 0.006 mg kg−1). However contrary results have also been reported.…”
Section: Uptake and Transport Of As In Rice Plantsmentioning
confidence: 95%
“…However contrary results have also been reported. For instance, Weber et al [13] also reported a much lower mean DMA (0.031 ± 0.010 mg kg −1 ) in rice bran under AWD compared to that under CF (0.149 ± 0.0622 mg kg −1 ) ( Table 1 ). In contrast, under CF, the anaerobic conditions in the soil promote the methylation of iAs to MMA.…”
Section: Uptake and Transport Of As In Rice Plantsmentioning
confidence: 95%
See 3 more Smart Citations